Row orientation effects on chemical composition and aromatic profile of Syrah winter wines - MOTA,Renata Vieira da (2021)
Abstract Sunlight and heating influence leaf and grape metabolism and therefore wine quality. As a recent management tool, no information exists on the effects of grapevine row orientation on the wine composition of Syrah vines within the context of double pruning management, a technique used to transfer the grape harvest from the wet summer to the dry winter season. This is a first attempt to investigate the wine composition from north-south- (NS) and east-west- (EW) oriented Syrah winter vines. EW wine samples had higher total acidity, residual sugars, alcohol and color hue, whereas NS wines exhibited higher content of color intensity, anthocyanins, total phenolics, total phenolic index, ashes and pH. The identification of volatile compounds was tentatively performed and demonstrated the presence of alkanes, volatile phenols and alkyl sulfide in NS wines, while butyrolactone and beta-damascenone were found mainly in EW wines. Row orientation contributed to wine composition and could be used as a management tool for obtaining individual wine styles.